Analysis of ICT For Asthma Patient Monitoring, A Scientific Literature Review 2015-2020 - Neyser Castillo-Obregón; Michael Cabanillas-Carbonell (Communications of International Proceedings, 2021)
Today respiratory diseases affect many people worldwide, this chronic disease is very common in the general population, so it should be considered a public health problem that should be followed up on this disease. For this reason, the study carried out is a review of the scientific literature, which includes 86 articles aiming to identify the factors to analyze and do a follow-up control of asthma disease, which were systematized by documents collected from the scientific databases IEEE Xplore, Ebsco, Science Direct, Scopus, according to the inclusion and exclusion criteria 32 articles were systematized. Showing ICTs that facilitate the monitoring of patients with asthma, concluding that the implementation of technology tools for monitoring diseases such as asthma allows us to reach a more accurate diagnosis.
Keywords: Monitoring; Analysis; Chronic; Asthma; Systematic Review.